2013
DOI: 10.1177/1071100712460197
|View full text |Cite
|
Sign up to set email alerts
|

Aircast Walking Boot and Below-Knee Walking Cast for Avulsion Fractures of the Base of the Fifth Metatarsal

Abstract: Level II, prospective comparative series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 10 publications
2
51
2
1
Order By: Relevance
“…One article included a different type of step test that involved maintaining balance on the involved limb while using the contralateral limb to step on and off a 15-cm step as quickly as possible [9]. Survey data of when patients reported return to driving were published in 14 articles [1,2,4,5,17,27,29,31,34,43,45,46,49,55]. …”
Section: Study Design and Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…One article included a different type of step test that involved maintaining balance on the involved limb while using the contralateral limb to step on and off a 15-cm step as quickly as possible [9]. Survey data of when patients reported return to driving were published in 14 articles [1,2,4,5,17,27,29,31,34,43,45,46,49,55]. …”
Section: Study Design and Populationsmentioning
confidence: 99%
“…Patients with a 5th metatarsal avulsion fracture reported a return to driving at 6 weeks when treated with a walking boot and 12 weeks after injury when treated with a short leg cast [55].…”
Section: Survey Measuresmentioning
confidence: 99%
“…An extensive evidence base exists with excellent outcomes following early mobilisation without the need for regular review. It has been demonstrated that treatment with a short leg cast leads to a significant delay in return to pre-injury levels when compared to functional treatment [7]. However, definitive management is usually only commenced at an orthopaedic fracture clinic within a few days from injury rather than at initial Background: Fifth metatarsal fractures are common, and the outcome with conservative treatment is generally very satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…This would include all zones described in the present study. A comparative study of the treatment of avulsion fractures in either a weightbearing cast or weightbearing boot was undertaken by Shahid et al (13) and published in 2013. No patients were treated with operative intervention.…”
Section: Discussionmentioning
confidence: 99%